PELATIHAN PEMBUATAN PUPUK KASCING SEBAGAI ALTERNATIF PUPUK ORGANIK UNTUK PENGUATAN USAHA BUMDES BRODONOYO KABUPATEN MALANG - Arifah, Sri Mursiani; Zakia, Aulia; Pangestika, Padhina (Universitas Padjadjaran, 2026)
Wonorejo Village possesses significant organic biomass potential from agricultural and household waste that has not yet been optimally utilized. This community service activity aimed to empower the Village-Owned Enterprise (BUMDes) “Bodronoyo” through training and assistance in the production of vermicompost. The activities were carried out through lectures, hands-on practice, discussions, and coaching clinics. The BUMDes was trained to produce vermicompost using organic waste, supported in the packaging and branding processes, and prepared to develop it as a sustainable business unit, with evaluations conducted at both the mid-point and the end of the program. The results showed that the BUMDes is capable of independently producing vermicompost and is ready to develop it as a sustainable business unit. The production of vermicompost fertilizer resulting from this training reached 100 kg. A total of seven participants attended the activity and demonstrated improved skills in utilizing organic waste. This initiative is expected to serve as a replicable model for other villages in organic waste management.Desa Wonorejo memiliki potensi biomassa organik dari limbah pertanian dan rumah tangga yang belum dimanfaatkan secara optimal. Kegiatan pengabdian ini bertujuan untuk memberdayakan Badan Usaha Milik Desa (Bumdes) “Bodronoyo” melalui pelatihan dan pendampingan pembuatan pupuk kascing (vermicompost). Kegiatan dilaksanakan melalui ceramah, praktik, diskusi, dan coaching clinic. Bumdes dilatih memproduksi kascing dari limbah organik, didampingi dalam proses pengemasan dan branding, serta dievaluasi pada pertengahan dan akhir kegiatan. Hasil menunjukkan bahwa Bumdes mampu memproduksi kascing secara mandiri dan siap mengembangkannya sebagai unit usaha berkelanjutan. Produksi pupuk kascing yang dihasilkan dari pelatihan ini sebanyak 100 kg. Jumlah peserta yang mengikuti kegiatan ini sebanyak tujuh orang dan mengalami peningkatan keterampilan dalam pemanfaatan limbah organik. Kegiatan ini diharapkan menjadi model replikasi bagi desa lain dalam pengelolaan limbah organik.